Targeting sphingosine kinase 1 attenuates bleomycin‐induced pulmonary fibrosis. Issue 4 (11th January 2013) - Huang, Long Shuang; Berdyshev, Evgeny; Mathew, Biji; Fu, Panfeng; Gorshkova, Irina A.; He, Donghong; Ma, Wenli; Noth, Imre; Ma, Shwu‐Fan; Pendyala, Srikanth; Reddy, Sekhar P.; Zhou, Tong; et al.
Abstract : Idiopathic pulmonary fibrosis (IPF) is a chronic and progressive interstitial lung disease, wherein transforming growth factor β (TGF‐β) and sphingosine‐1‐phosphate (S1P) contribute to the pathogenesis of fibrosis. However, the in vivo contribution of sphingosine kinase (SphK) in fibrotic processes has not been documented. Microarray analysis of blood mononuclear cells from patients with IPF and SphK1‐ or SphK2‐knockdown mice and SphK inhibitor were used to assess the role of SphKs in fibrogenesis. The expression of SphK1/2 negatively correlated with lung function and survival in patients with IPF. Also, the expression of SphK1 was increased in lung tissues from patients with IPF and bleomycin‐challenged mice. Knockdown of SphK1, but not SphK2, increased survival and resistance to pulmonary fibrosis in bleomycin‐challenged mice. Administration of SphK inhibitor reduced bleomycin‐induced mortality and pulmonary fibrosis in mice. Knockdown of SphK1 or treatment with SphK inhibitor attenuated S1P generation and TGF‐β secretion in a bleomycin‐induced lung fibrosis mouse model that was accompanied by reduced phosphorylation of Smad2 and MAPKs in lung tissue. In vitro, bleomycin‐induced expression of SphK1 in lung fibroblast was found to be TGF‐β dependent. Taken together, these data indicate that SphK1 plays a critical role in the pathology of lung fibrosis and is a novel therapeutic target.—Huang, L. S., Berdyshev, E., Mathew, B., Fu, P., Gorshkova, I. A., He, D., Ma, W., Noth, I., Ma, S.‐F., Pendyala, S., Reddy, S. P., Zhou, T., Zhang, W., Garzon, S. A., Garcia, J. G. N., Natarajan, V. Targeting sphingosine kinase 1 attenuates bleomycin‐induced pulmonary fibrosis. FASEB J. 27, 1749–1760 (2013). www.fasebj.org